Diffuse Leptomeningeal Glioneuronal Tumors: A New Entity? - Gardiman, Marina Paola (Brain Pathol, 2009)
The peculiar radiological and pathological findings of four pediatric cases admitted to the University Hospital of Padua between 1990 and 2007 are described. In all cases, the contrast‐enhanced head and spine magnetic resonance images revealed thickened and abnormally enhancing subarachnoid spaces particularly at the level of basal cisterns and interhemispheric fissure. Furthermore, small cystic lesions scattered throughout the brain and mainly in the cerebellum were also visible. All patients were missing a well‐defined intraparenchymal mass, although during the follow‐up a small intramedullary lesion appeared within the cervical spine in two and subsequently in the frontal horn of the left lateral ventricle in one of those. All patients presented an indolent long‐term follow‐up. Histologically, the tumors were composed by a monotonous population of cells arranged in straight lines or in small lobules. The cells were characterized by round to oval nuclei with finely granular dispersed chromatin, inconspicuous nucleoli with oligodendrocyte‐like features. The morphological and immunohistochemical findings suggested in all cases a “glioneuronal commitment” of the tumors. Because of the unique similar clinical and neuroradiological characteristics, we propose this small series of tumors as a new possible distinct pathological and clinical entity.